2022
DOI: 10.1177/02654075221119429
|View full text |Cite
|
Sign up to set email alerts
|

Self-disclosure in social media and psychological well-being: A meta-analysis

Abstract: Self-disclosure in social media and psychological well-being have been theorized to mutually influence each other. The vibrant research on this issue, however, presents mixed results, calling for a synthesis of the empirical evidence. To this end, we conducted a meta-analysis with 38 empirical studies to systematically examine the nature of the relationship between social media self-disclosure and psychological well-being. We adopted a multidimensional perspective of self-disclosure to scrutinize how the quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 109 publications
1
13
0
2
Order By: Relevance
“…An overwhelming amount of literature has focused on the negative consequences of SNS, including (a) intensive use of SNS, which brings experiences of time displacement and overload ( van der Schuur et al, 2019 ; Prestin and Nabi, 2020 ; Wang et al, 2021 ); (b) problematic use of SNS, which increases levels of psychological distress, work exhaustion, and suicidal ideation and suicide attempts ( McConnell et al, 2018 ; Froehlich et al, 2020 ); and (c) upward comparison and envy, led by the tendency to compare with the perfected content of others ( Batenburg and Das, 2015 ; Spitzer et al, 2022 ). On the other hand, accumulating research has highlighted SNS’ positive effects, including (a) online social support, which serves as a coping mechanism against negative thoughts and events ( Oh et al, 2014 ; Bi et al, 2020 ); (b) reduced riskiness of self-disclosure, facilitated by SNS’ publicity, broad reach, usability, and immediacy ( Pan et al, 2017 ; Li et al, 2019 ; Chu et al, 2022 ); and (c) inspiration and enjoyment, when users reach out for social relationship maintenance ( Kim and Kim, 2020 ; Myrick and Willoughby, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…An overwhelming amount of literature has focused on the negative consequences of SNS, including (a) intensive use of SNS, which brings experiences of time displacement and overload ( van der Schuur et al, 2019 ; Prestin and Nabi, 2020 ; Wang et al, 2021 ); (b) problematic use of SNS, which increases levels of psychological distress, work exhaustion, and suicidal ideation and suicide attempts ( McConnell et al, 2018 ; Froehlich et al, 2020 ); and (c) upward comparison and envy, led by the tendency to compare with the perfected content of others ( Batenburg and Das, 2015 ; Spitzer et al, 2022 ). On the other hand, accumulating research has highlighted SNS’ positive effects, including (a) online social support, which serves as a coping mechanism against negative thoughts and events ( Oh et al, 2014 ; Bi et al, 2020 ); (b) reduced riskiness of self-disclosure, facilitated by SNS’ publicity, broad reach, usability, and immediacy ( Pan et al, 2017 ; Li et al, 2019 ; Chu et al, 2022 ); and (c) inspiration and enjoyment, when users reach out for social relationship maintenance ( Kim and Kim, 2020 ; Myrick and Willoughby, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Utz indicated that positive and entertaining self-disclosure on SNSs increased the feeling of connection with friends [ 3 ]. Recently, researchers have focused on the effects of SNS-specific self-disclosure, rather than on SNS self-disclosure in general [ 4 , 5 ]; for example, the effect of the valence of self-disclosed content on Facebook on interactions with other individuals [ 6 ]. Therefore, there is a growing tendency for researchers to focus on how the use of SNSs affects adolescents’ physical and mental development, especially the specific self-disclosure behaviors seen commonly.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, forming and strengthening social relations is a fundamental purpose of SNS users, and SNSs provide a handy way for adolescents to maintain and develop relationships with their offline friends [ 8 ]. Research indicates that using SNSs, especially disclosing and expressing personal information on SNSs, can strengthen social ties and enhance closeness and connectedness between users and friends or acquaintances [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations